Double-coated lithium nickel cobalt manganese oxide and preparation method thereof, positive electrode material and lithium ion battery

By double-coated lithium nickel cobalt manganese oxide with nickel fluoride and carbon, the problem of capacity attenuation of high-nickel layered positive electrode materials in long-term circulation and poor Coulomb efficiency for the first time is solved, and significant cycling performance and Coulomb efficiency are achieved.

CN119612612AActive Publication Date: 2025-03-14WUHAN INSTITUTE OF MARINE ELECTRIC PROPULSION (THE 712TH RESEARCH INSTITUTE OF CHINA STATE SHIPBUILDING CORP LTD)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411735041.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

High-nickel layered cathode materials have problems of capacity attenuation and poor first-time Coulomb efficiency during long-term cycles, and the existing cladding materials such as AlF3 have small ionic conductivity, resulting in a large interface impedance and affecting charge transport.

Method used

The lithium nickel-cobalt-manganese oxide is double-coated with nickel fluoride (NiF2) and carbon (C) to prevent direct contact between the positive electrode material and the electrolyte through the NiF2 coating layer, and the conductivity is improved through the carbon coating layer and the interface impedance is reduced.

Benefits of technology

The cycling performance and first-time Coulomb efficiency of the ternary cathode material are significantly improved, the electrochemical performance of the material is improved, and the preparation process is good repeatability and has a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612612A_ABST
    Figure CN119612612A_ABST
Patent Text Reader

Abstract

The invention discloses a double-coated lithium nickel cobalt manganese oxide and a preparation method thereof, a positive electrode material and a lithium ion battery. The preparation method of the double-coated lithium nickel cobalt manganese oxide comprises the following steps: (1) uniformly mixing nickel acetate and absolute ethyl alcohol to obtain a solution; adding a lithium nickel cobalt manganese oxide into the solution, uniformly dispersing, adding an ammonium fluoride aqueous solution, reacting, and washing and drying a precipitate (NiF2) obtained by the reaction; and (2) mixing the sample dried in the step (1) with a carbon source, carrying out sufficient ball milling, and carrying out heat treatment after ball milling to prepare the double-coated lithium nickel cobalt manganese oxide. The method provided by the invention not only can improve the cycle performance of the layered ternary positive electrode material under high-voltage charging and discharging (such as 2.8-4.5 V), but also can improve the first coulombic efficiency of the layered ternary positive electrode material, and has the advantages of simple and feasible preparation method and strong universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion batteries, and in particular relates to a double-coated lithium nickel cobalt manganese oxide and a preparation method thereof, a positive electrode material and a lithium ion battery. Background Art

[0002] Layered nickel-cobalt-manganese oxide LiNi 1-x-y Co x Mn y O2 is one of the most widely used cathode materials for lithium-ion batteries in commercial applications. 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) and LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), etc., have attracted widespread attention due to their advantages such as low cost and high specific capacity. The charge and discharge specific capacity of ternary positive electrode materials can be further improved by increasing the charge and discharge cut-off voltage. However, the problems of capacity attenuation and poor first coulombic efficiency of layered positive electrode materials with high nickel content in long-term cycles under high pressure are more prominent.

[0003] At present, there are literature reports that the cycling performance of high-nickel ternary layered cathode materials can be improved by coating with oxides. For example, Zang M, Hu G, Wu L et al. (Electrochimica Acta, 2017, 232:80–88) improved the cycling performance of LiN by coating TiO2 on the surface. 0.5 Co 0.2 Mn 0.3 O2 cycling performance; Shi Y, Zhang M, Qian D et al. (ElectrochimicaActa, 2016, 203:154-161) improved the cycling performance of LiN by coating with Al2O3 0.5 Co 0.2 Mn 0.3 O2 cycle performance. However, since the electrolyte currently used contains lithium salt (LiPF6), during the long-term cycle of the battery, the byproduct hydrogen fluoride (HF) produced by partial decomposition of the electrolyte will corrode the coating layer, causing the battery cycle performance to gradually deteriorate. Therefore, it is necessary to find a material that is more stable in the electrolyte to coat the ternary positive electrode material. Due to the property that fluoride does not react with HF, it has been reported that LiN coated with AlF3 0.5 Co 0.2 Mn 0.3O2 can improve the cycle performance of high nickel cathode materials. For example, Yang K, Fan LZ, Guo J et al. (Electrochimica Acta, 2012, 63:363-368) improved the cycle performance of LiN by coating with AlF3. 0.5 Co 0.2 Mn 0.3 The first coulombic efficiency and cycle performance of O2. However, due to the low ionic conductivity of AlF3, the coating layer impedance is large, the charge transfer efficiency at the three-phase interface is reduced, and the discharge depth of the positive electrode material is adversely affected. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a double-coated lithium nickel cobalt manganese oxide and its preparation method, positive electrode material and lithium ion battery. The present invention adopts nickel fluoride and carbon (NiF2 and C) to double-coat lithium nickel cobalt manganese oxide, and the prepared positive electrode material has good cycle stability and first coulomb efficiency. Specifically, in order to improve the conductivity and interfacial charge transfer of the positive electrode material, the present invention adopts a double coating method of NiF2 and carbon-based materials. NiF2 has a higher conductivity than AlF3, but it may still increase the interface impedance when used alone. Therefore, the introduction of a carbon-based coating layer with good conductivity can effectively reduce the interface impedance, thereby improving the electrochemical performance of the material.

[0005] The purpose of the present invention is achieved through the following technical solutions: A method for preparing double-coated lithium nickel cobalt manganese oxide comprises the following steps: (1) nickel acetate and anhydrous ethanol are mixed uniformly to obtain a solution; lithium nickel cobalt manganese oxide is added to the solution, and after being uniformly dispersed, an aqueous solution of ammonium fluoride is added to react, and the precipitate (NiF2) obtained by the reaction is washed and then dried; (2) The dried sample in step (1) is mixed with a carbon source and fully ball-milled. After ball-milling, the mixture is heat-treated to obtain a double-coated lithium nickel cobalt manganese oxide.

[0006] Preferably, in step (1), nickel acetate is introduced in the form of Ni(CH3COO)2·4H2O.

[0007] Preferably, in step (1), the lithium nickel cobalt manganese oxide is LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0008] Preferably, the mass ratio of Ni(CH3COO)2·4H2O to anhydrous ethanol is 1:120-200.

[0009] Preferably, in step (1), the mass ratio of lithium nickel cobalt manganese oxide to theoretically generated NiF2 is 99.6:0.4 to 98.8:1.2.

[0010] Preferably, in step (1), the washing method is: repeatedly washing with anhydrous ethanol for 3 to 4 times.

[0011] Preferably, in step (1), the method of uniformly dispersing the sample is to fully disperse the sample by ultrasonication.

[0012] Preferably, in step (1), the drying temperature is 70-80° C. and the drying time is 8-10 hours.

[0013] Preferably, in step (1), the mass ratio of lithium nickel cobalt manganese oxide to the carbon in the carbon source in step (2) is 99.5:0.5 to 98.5:1.5.

[0014] Preferably, in step (2), the carbon source is at least one of sucrose, glucose and cellulose; more preferably, the cellulose is carboxymethyl cellulose.

[0015] Preferably, in step (2), the heat treatment conditions are: introducing argon at a rate of 2 L / min, raising the temperature to 450-550°C at a rate of 2-4°C / min and keeping the temperature for 2-4h.

[0016] The double-coated lithium nickel cobalt manganese oxide is prepared by the preparation method of the double-coated lithium nickel cobalt manganese oxide.

[0017] A positive electrode material comprises the above double-coated lithium nickel cobalt manganese oxide.

[0018] A lithium-ion battery comprises the above-mentioned positive electrode material.

[0019] Compared with the prior art, the beneficial effects of the present invention include: The present invention proposes a method for improving the electrochemical performance of high-nickel layered positive electrode materials by double coating with nickel fluoride (NiF2) and carbon (C). NiF2 is coated on the surface of the positive electrode material, which can effectively prevent the direct contact between the positive electrode material and the electrolyte, thereby improving the cycle performance of the material. However, NiF2, like traditional fluorides such as AlF3 and MgF2, has the problem of low electronic conductivity. The simple use of fluoride coating will have a certain impact on the charge transfer at the interface of the positive electrode material. Therefore, the present application proposes to use a highly conductive carbon material for secondary coating while using nickel fluoride coating, so as to improve the conductivity of the coating layer, thereby improving the shortcomings of pure fluoride coating. The method of the present invention not only significantly improves the cycle performance of the ternary positive electrode material, but also effectively improves the first coulomb efficiency of the material, and the preparation process has good repeatability and a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The LiNi described in Comparative Example 1 0.5 Co 0.2 Mn 0.3 A comparison chart of the first charge and discharge curves of the battery prepared by the double-coated lithium nickel cobalt manganese oxide described in O2 and Example 5 in the voltage range of 2.8V to 4.5V, wherein a corresponds to Example 1 and b corresponds to Example 5.

[0021] Figure 2 The LiNi described in Comparative Example 1 0.5 Co 0.2 Mn 0.3 Comparison of the cycle curves of the battery prepared by the double-coated lithium nickel cobalt manganese oxide described in Example 1 and Example 5 in the voltage range of 2.8V to 4.5V, wherein a corresponds to Example 1 and b corresponds to Example 5. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] Before the electrochemical performance characterization of the following examples and comparative examples, the corresponding positive electrode materials need to be assembled into CR2025 button batteries, in which metallic lithium is used as the negative electrode material and 1 mol / L LiPF6 DMC:EC (1:1) solution is used as the electrolyte.

[0024] Comparative Example 1 LiNi 0.5 Co 0.2 Mn 0.3 O2 was used as the positive electrode material, and its electrochemical performance was characterized. -1 The first charge capacity was 220.7 mAh / g, the discharge capacity was 185.8 mAh / g, and the first coulombic efficiency was 84.2%. -1 The current density was tested and the initial discharge capacity was 174 mAh / g. After 50 cycles, the discharge capacity was 143 mAh / g and the capacity retention rate was 82.2%.

[0025] Example 1 A method for preparing double-coated lithium nickel cobalt manganese oxide, comprising the following steps: (1) Weigh 0.3 g Ni(CH3COO)2·4H2O and 60 g anhydrous ethanol, mix and stir for 30 min to dissolve Ni(CH3COO)2·4H2O to obtain a solution; weigh 29.022 g LiNi 0.5 Co 0.2 Mn 0.3 O2 was put into the solution and ultrasonically dispersed for 30 minutes. 0.089g NH4F and 10g deionized water were weighed, mixed and stirred for 10 minutes to prepare an NH4F aqueous solution; the prepared NH4F aqueous solution was slowly added dropwise to the uniform solution dispersed by ultrasonication, and the obtained precipitate was washed with anhydrous ethanol for 3 to 4 times and dried at 70°C for 8 hours.

[0026] (2) The dried sample of step (1) was mixed with 1.106 g of glucose and fully ball-milled. After ball-milling, the sample was heated to 450° C. at a rate of 2° C. / min and heat-treated for 2 h under an argon gas flow of 2 L / min to obtain a ternary positive electrode material LiNi double-coated with nickel fluoride and carbon. 0.5 Co 0.2 Mn 0.3 O2 (NCM523), namely the double-coated lithium nickel cobalt manganese oxide.

[0027] Compared with Comparative Example 1, the LiNi 0.5 Co 0.2 Mn 0.3 O2, in the voltage range of 2.8V to 4.5V, at 15mAg -1 The first charge capacity was 210.6 mAh / g, the discharge capacity was 181.5 mAh / g, and the first coulombic efficiency was 86.2%. -1 The initial discharge capacity was 168.5 mAh / g. After 50 cycles, the discharge capacity was 147.3 mAh / g, and the capacity retention rate was 87.4%. These results show that the coating treatment significantly improves the LiNi 0.5 Co 0.2 Mn 0.3 First coulombic efficiency and cycling performance of O2.

[0028] Example 2 A method for preparing double-coated lithium nickel cobalt manganese oxide, comprising the following steps: (1) Weigh 0.3 g Ni(CH3COO)2·4H2O and 48 g anhydrous ethanol, mix and stir for 40 min to dissolve Ni(CH3COO)2·4H2O to obtain a solution; weigh 14.453 g LiNi 0.5 Co0.2 Mn 0.3 O2 was added to the solution and ultrasonically dispersed for 35 minutes. 0.089g NH4F and 10g deionized water were weighed, mixed and stirred for 10 minutes to prepare an NH4F aqueous solution; the prepared NH4F aqueous solution was slowly added dropwise to the uniform solution dispersed by ultrasonication, and the obtained precipitate was washed with anhydrous ethanol for 3 to 4 times and dried at 75°C for 9 hours.

[0029] (2) The dried sample of step (1) was mixed with 0.182 g of glucose and fully ball-milled. After ball-milling, the sample was heated to 500° C. at a rate of 3° C. / min and heat-treated for 2 h under an argon gas flow of 2 L / min to obtain a ternary positive electrode material LiNi double-coated with nickel fluoride and carbon. 0.5 Co 0.2 Mn 0.3 O2 (NCM523), namely the double-coated lithium nickel cobalt manganese oxide.

[0030] Compared with Comparative Example 1, the LiNi 0.5 Co 0.2 Mn 0.3 O2, in the voltage range of 2.8V to 4.5V, at 15mAg -1 The current density was tested, the first charge capacity was 212.0mAh / g, the discharge capacity was 186.8mAh / g, and the first coulombic efficiency was 88.1%; in the voltage range of 2.8V to 4.5V, at 150mAg -1 The initial discharge capacity was 170.1 mAh / g. After 50 cycles, the discharge capacity was 153.2 mAh / g, and the capacity retention rate was 90.1%. These results show that the coating treatment significantly improves the LiNi 0.5 Co 0.2 Mn 0.3 First coulombic efficiency and cycling performance of O2.

[0031] Example 3 A method for preparing double-coated lithium nickel cobalt manganese oxide, comprising the following steps: (1) Weigh 0.3 g Ni(CH3COO)2·4H2O and 36 g anhydrous ethanol, mix and stir for 50 min to dissolve Ni(CH3COO)2·4H2O to obtain a solution; weigh 9.596 g LiNi 0.5 Co 0.2 Mn 0.3O2 was put into the solution and ultrasonically dispersed for 40 minutes. 0.089g NH4F and 10g deionized water were weighed, mixed and stirred for 10 minutes to prepare an NH4F aqueous solution; the prepared NH4F aqueous solution was slowly added dropwise to the uniform solution dispersed by ultrasonication, and the obtained precipitate was washed with anhydrous ethanol for 3 to 4 times and dried at 80°C for 10 hours.

[0032] (2) The dried sample of step (1) was mixed with 0.230 g of sucrose and fully ball-milled. After ball-milling, the sample was heated to 550° C. at a rate of 4° C. / min and heat-treated for 4 h under an argon gas flow of 2 L / min to obtain a ternary positive electrode material LiNi double-coated with nickel fluoride and carbon. 0.5 Co 0.2 Mn 0.3 O2 (NCM523), namely the double-coated lithium nickel cobalt manganese oxide.

[0033] Compared with Comparative Example 1, the LiNi 0.5 Co 0.2 Mn 0.3 O2, in the voltage range of 2.8V to 4.5V, at 15mAg -1 The current density was tested, the first charge capacity was 207.8mAh / g, the discharge capacity was 178.7mAh / g, and the first coulombic efficiency was 86.0%; in the voltage range of 2.8V to 4.5V, at 150mAg -1 The initial discharge capacity was 165.2 mAh / g. After 50 cycles, the discharge capacity was 141.3 mAh / g, and the capacity retention rate was 85.5%. These results show that the coating treatment significantly improves the LiNi 0.5 Co 0.2 Mn 0.3 First coulombic efficiency and cycling performance of O2.

[0034] Example 4 A method for preparing double-coated lithium nickel cobalt manganese oxide, comprising the following steps: (1) Weigh 0.3 g Ni(CH3COO)2·4H2O and 60 g anhydrous ethanol, mix and stir for 30 min to dissolve Ni(CH3COO)2·4H2O to obtain a solution; weigh 29.022 g LiNi 0.5 Co 0.2 Mn 0.3O2 was put into the solution and ultrasonically dispersed for 30 minutes. 0.089g NH4F and 10g deionized water were weighed, mixed and stirred for 10 minutes to prepare an NH4F aqueous solution; the prepared NH4F aqueous solution was slowly added dropwise to the uniform solution dispersed by ultrasonication, and the obtained precipitate was washed with anhydrous ethanol for 3 to 4 times and dried at 70°C for 8 hours.

[0035] (2) The dried sample of step (1) was mixed with 0.697 g of sucrose and fully ball-milled. After ball-milling, the sample was heated to 500° C. at a rate of 2° C. / min and heat-treated for 3 h under an argon gas flow of 2 L / min to obtain a ternary positive electrode material LiNi double-coated with nickel fluoride and carbon. 0.5 Co 0.2 Mn 0.3 O2 (NCM523), namely the double-coated lithium nickel cobalt manganese oxide.

[0036] Compared with Comparative Example 1, the LiNi 0.5 Co 0.2 Mn 0.3 O2, in the voltage range of 2.8V to 4.5V, at 15mAg -1 The current density was tested, the first charge capacity was 215.0mAh / g, the discharge capacity was 191.4mAh / g, and the first coulombic efficiency was 89.0%; in the voltage range of 2.8V to 4.5V, at 150mAg -1 The initial discharge capacity was 168.4 mAh / g. After 50 cycles, the discharge capacity was 150.2 mAh / g, and the capacity retention rate was 89.2%. These results show that the coating treatment significantly improves the LiNi 0.5 Co 0.2 Mn 0.3 First coulombic efficiency and cycling performance of O2.

[0037] Example 5 A method for preparing double-coated lithium nickel cobalt manganese oxide, comprising the following steps: (1) Weigh 0.3 g Ni(CH3COO)2·4H2O and 48 g anhydrous ethanol, mix and stir for 40 min to dissolve Ni(CH3COO)2·4H2O to obtain a solution; weigh 14.453 g LiNi 0.5 Co 0.2 Mn 0.3O2 was added to the solution and ultrasonically dispersed for 35 minutes. 0.089g NH4F and 10g deionized water were weighed, mixed and stirred for 10 minutes to prepare an NH4F aqueous solution; the prepared NH4F aqueous solution was slowly added dropwise to the uniform solution dispersed by ultrasonication, and the obtained precipitate was washed with anhydrous ethanol for 3 to 4 times and dried at 75°C for 9 hours.

[0038] (2) The dried sample of step (1) was mixed with 0.491 g of carboxymethyl cellulose and fully ball-milled. After ball-milling, the sample was heated to 550°C at a rate of 3°C / min and heat-treated for 4 h under an argon gas flow of 2 L / min to obtain a ternary positive electrode material LiNi double-coated with nickel fluoride and carbon. 0.5 Co 0.2 Mn 0.3 O2 (NCM523), namely the double-coated lithium nickel cobalt manganese oxide.

[0039] Compared with Comparative Example 1, the LiNi 0.5 Co 0.2 Mn 0.3 O2, in the voltage range of 2.8V to 4.5V, at 15mAg -1 The current density was tested, the first charge capacity was 212mAh / g, the discharge capacity was 187.5mAh / g, and the first coulombic efficiency was 88.4%; in the voltage range of 2.8V to 4.5V, at 150mAg -1 The initial discharge capacity was 169.9 mAh / g. After 50 cycles, the discharge capacity was 154.8 mAh / g, and the capacity retention rate was 91.1%. These results show that the coating treatment significantly improves the LiNi 0.5 Co 0.2 Mn 0.3 First coulombic efficiency and cycling performance of O2.

[0040] Figure 1 The LiNi described in Comparative Example 1 0.5 Co 0.2 Mn 0.3 A comparison chart of the first charge and discharge curves of the battery prepared by the double-coated lithium nickel cobalt manganese oxide described in O2 and Example 5 in the voltage range of 2.8V to 4.5V, wherein a corresponds to Example 1 and b corresponds to Example 5.

[0041] Figure 2 The LiNi described in Comparative Example 1 0.5 Co 0.2 Mn 0.3Comparison of the cycle curves of the battery prepared by the double-coated lithium nickel cobalt manganese oxide described in Example 1 and Example 5 in the voltage range of 2.8V to 4.5V, wherein a corresponds to Example 1 and b corresponds to Example 5.

[0042] See also Figure 1~2 We know that LiNi is double coated with nickel fluoride (NiF2) and carbon (C). 0.5 Co 0.2 Mn 0.3 O2, which can significantly improve its first coulombic efficiency and cycle performance.

[0043] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing double-coated lithium nickel cobalt manganese oxide, characterized in that: The steps include: (1) nickel acetate and anhydrous ethanol are mixed uniformly to obtain a solution; lithium nickel cobalt manganese oxide is added to the solution, and after being uniformly dispersed, an ammonium fluoride aqueous solution is added to react, and a precipitate obtained by the reaction is washed and then dried; (2) The dried sample in step (1) is mixed with a carbon source and fully ball-milled, and then heat-treated after ball-milling to obtain the double-coated lithium nickel cobalt manganese oxide.

2. The method for preparing double-coated lithium nickel cobalt manganese oxide according to claim 1, characterized in that: The nickel acetate in step (1) is introduced in the form of Ni(CH3COO)2·4H2O; The lithium nickel cobalt manganese oxide in step (1) is LiNi 0.5 Co 0.2 Mn 0.3 O2.

3. The method for preparing double-coated lithium nickel cobalt manganese oxide according to claim 2, characterized in that: The mass ratio of Ni(CH3COO)2·4H2O to anhydrous ethanol is 1:120-200.

4. The method for preparing double-coated lithium nickel cobalt manganese oxide according to claim 3, characterized in that: The mass ratio of the lithium nickel cobalt manganese oxide to the theoretically generated NiF2 in step (1) is 99.6:0.4 to 98.8:1.

2.

5. The method for preparing double-coated lithium nickel cobalt manganese oxide according to claim 1, characterized in that: The washing method in step (1) is: washing repeatedly 3 to 4 times with anhydrous ethanol; The method of uniform dispersion in step (1) is to fully disperse the sample by ultrasonication.

6. The method for preparing double-coated lithium nickel cobalt manganese oxide according to claim 1, characterized in that: The drying temperature in step (1) is 70-80°C and the drying time is 8-10 hours; The mass ratio of the lithium nickel cobalt manganese oxide in step (1) to the carbon in the carbon source in step (2) is 99.5:0.5 to 98.5:1.

5.

7. The method for preparing double-coated lithium nickel cobalt manganese oxide according to claim 1, characterized in that: The carbon source in step (2) is at least one of sucrose, glucose and cellulose; The heat treatment conditions in step (2) are as follows: introducing argon at a rate of 2 L / min, raising the temperature to 450-550°C at a rate of 2-4°C / min and keeping the temperature for 2-4 hours.

8. Double-coated lithium nickel cobalt manganese oxide prepared by the method for preparing double-coated lithium nickel cobalt manganese oxide according to any one of claims 1 to 7.

9. A positive electrode material, characterized in that: Comprising the double-coated lithium nickel cobalt manganese oxide as described in claim 8.

10. A lithium ion battery, characterized in that: Contains the positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Double-coated manganese-base layered lithium-rich material and preparation method thereof

    CN105161686A

  • Preparation method of lithium ion battery composite cathode material

    CN107492636A

  • Modified high-nickel ternary material, preparation method and application thereof, and lithium ion battery positive electrode material

    CN116207266A

  • Metal fluoride coated lithium-rich manganese-based positive electrode material and preparation method thereof

    CN116741963A

  • Composite positive electrode material and preparation method and application thereof

    US20230411609A1